Extracorporeal carbon dioxide removal for the treatment of acute hypoxaemic respiratory failure: the REST RCT - James J McNamee; Ashley Agus; Andrew J Boyle; Colette Jackson; Cliona McDowell; Jeanette Haglund; Danny F McAuley (Health Technology Assessment)
Background In patients who require mechanical ventilation for acute hypoxaemic respiratory failure, further reduction in tidal volumes, compared with conventional low tidal volume ventilation, may improve outcomes. Objective To determine whether using extracorporeal carbon dioxide removal improves outcomes in patients with acute hypoxaemic respiratory failure and is cost-effective. Design A multicentre, randomised, allocation-concealed, open-label, pragmatic clinical trial. Setting Fifty-one intensive care units across the United Kingdom. Participants Four hundred and twelve adult patients receiving mechanical ventilation for acute hypoxaemic respiratory failure, of a planned sample size of 1120. Interventions Lower tidal volume ventilation facilitated by extracorporeal carbon dioxide removal for at least 48 hours (n = 202) or standard care with conventional low tidal volume ventilation (n = 210). Main outcome measures All-cause mortality 90 days. Secondary outcomes included ventilator-free days; adverse events; extracorporeal membrane oxygenation use; long-term mortality; health-related quality of life; health service costs; long-term respiratory morbidity. Results The trial was stopped early because of futility and feasibility. The 90-day mortality rate was 41.5% in the extracorporeal carbon dioxide removal group versus 39.5% in the standard care group (risk ratio 1.05, 95% confidence interval 0.83 to 1.33; difference 2.0%, 95% confidence interval  − 7.6% to 11.5%; p = 0.68). There were significantly fewer mean ventilator-free days in the extracorporeal carbon dioxide removal group compared with the standard care group (7.1, 95% confidence interval 5.9 to 8.3) versus (9.2, 95% confidence interval 7.9 to 10.4) days; mean difference, −2.1 (95% confidence interval −3.8 to −0.3; p = 0.02). Serious adverse events were reported for 62 patients (31%) in extracorporeal carbon dioxide removal group and 18 (9%) in the standard care group, including intracranial haemorrhage in 9 patients (4.5%) versus 0 (0%) and bleeding at other sites in 6 (3.0%) versus 1 (0.5%) in the extracorporeal carbon dioxide removal group versus the control group. Two-year mortality data were available for 95% of patients. There was no difference in the time to death between groups (hazard ratio 1.08, 95% confidence interval 0.81 to 1.44; log-rank test p = 0.61). There was no difference in long-term outcomes between groups. There was no difference in quality-adjusted life-years at 12 months (mean difference −0.01, 95% confidence interval −0.06 to 0.05). Total 12-month costs were statistically significantly higher in the extracorporeal carbon dioxide removal group (mean difference £7668.76, 95% confidence interval £159.75 to £15,177.77). Secondary analyses indicated there may be heterogeneity of treatment effect based on physiological characteristics of the patients. A systematic review supported these findings. Limitations Only 6% of screened patients were included in the study; most sites were naive to the intervention before the study commenced; other aspects of care were not standardised in each group, because this was a pragmatic trial; the trial may have been underpowered to detect a clinically important difference, because the trial was stopped early; blinding to the clinicians or patients was not possible. Conclusions There were no short- or long-term benefits found, and the device was associated with higher cost and potentially significant complications. We would advise against using this device in addition to standard care for the treatment of patients with hypoxaemic respiratory failure, outside of future clinical trials. Future work Future studies could further explore whether different patient populations receiving a larger ‘dose’ of from extracorporeal carbon dioxide removal might benefit, use core outcome sets and collect broader long-term outcomes and consider measuring patients’ health-related quality of life at the soonest opportunity after regaining capacity. Funding This synopsis presents independent research funded by the National Institute for Health and Care Research (NIHR) Health Technology Assessment programme as award number 13/143/02. Plain language summary Why did we do this study? Many patients admitted to the intensive care unit need a breathing machine, or ventilator, to help them breathe and ensure that enough oxygen gets into their blood and carbon dioxide is removed. When people are critically ill, their lungs often fail; this is termed ‘acute respiratory failure’. Currently, there are no specific treatments other than placing the person on a ventilator to help bellow air in and out of the lungs, but this may damage the lungs and prevent healing and repair. There is currently a device called extracorporeal carbon dioxide removal, which could help ventilation by removing carbon dioxide from the blood and cause less damage to the lungs. What did we do? We ran a study in intensive care units across the United Kingdom to compare extracorporeal carbon dioxide removal with standard care. We also wanted to find out if extracorporeal carbon dioxide removal reduced the time patients spent on a ventilator and in hospital, improved quality of life and was good value for money for the National Health Service. We aimed to recruit 1120 participants; however, the study closed early due to the extracorporeal carbon dioxide removal being found to be ineffective. From May 2016 to December 2019, we recruited 412 participants and randomly allocated them to be treated with extracorporeal carbon dioxide removal (202) or standard ventilation (210). What did we find? In conclusion, the use of a device that removes carbon dioxide from the blood and allows for gentler mechanical ventilation of the lungs in adult patients had no effect on the death rate of patients after 90 days. There was also no effect on other short- or long-term outcomes. The device was associated with higher costs and potentially significant complications. What does this mean for participants with acute respiratory failure? We suggest this device is not used for routine care in patients with hypoxaemic respiratory failure, and if intensive care units are already using this device, they should consider discontinuing its use for this indication.